First sighting of a pelagic seabird entangled in a disposable COVID-19 facemask in the Mediterranean Sea - KARRIS, GEORGIOS; SAVVA, IOANNIS; KAKALIS, ELEFTHERIOS; BAIRAKTARIDOU, KYRIAKI; ESPINOSA, CHLOE; SMITH, Matthew Stephen; BOTSIDOU, PETROULA; MOSCHOUS, STAMATIOS; VOULGARIS, Marios-Dimitrios; PEPPA, ELENI; PANAYIDES, PANICOS; HADJISTYLLIS, HARIS; et al. (Mediterranean Marine Science, 2023)
Seabirds are increasingly recognized as important bio-indicators of marine ecosystems that are useful in assessing environmental disturbance on the marine biota. Over the period 2020-22 and during the first national systematic recording of the sea waters surrounding the Republic of Cyprus, we recorded the spatio-temporal presence, abundance and behaviour of seabirds using the ESAS (European Seabirds At Sea) methodology. Here we present the observation of an accidentally entangled pelagic seabird in COVID-19 material which to the best of our knowledge is the first incident in the Mediterranean Basin. The systematic recording of entangled marine birds in personal protective equipment (PPE) used to prevent COVID-19 transmission worldwide seems to be of crucial importance for one of the most important emerging threats for the conservation of seabirds at global scale.